Recuperación urbano paisajística del río Combeima entre el tramo puente Cajamarca – puente Las Brisas Ibagué-Tolima. (2021)
The problem that the area related to the Combeima river has is the adjoining informal housing, which are in an environmental protection zone of the river for its conservation, in addition to directly polluting with residues and/or garbage that affect and pollute the river; Consequent to this what is wanted to be given to justify by means of an entity like Cortolima, which makes a study evaluating the geographical index of environmental protection (IGCA) is the system the which shows us the area of ​​deterioration or invasion of the environmental protection of the water basin that is discriminated against with the criteria good, fair, and bad, since this section of the river is in a bad state which indicates the invasion of this space of environmental protection.